ARC FAULT CIRCUIT INTERRUPTER - DVORAK, ROBERT F; SCOTT, GARY W; GRATTAN, BRIAN G; WONG, KON B; HAUN, ANDY A (2005)
A system for producing a simulated ground fault when arcing is present in an electrical circuit includes a sensor which monitors the electrical circuit. An arcing fault detection circuit determines whether an arcing fault is present in response to the sensor and produces a trip signal in response to a determination that an arcing fau lt is present in the electrical circuit. A ground fault simulator circuit produces a simulate d ground fault in response to the trip signal.